FORECASTING RELIGIOUS TOURISM IN KARBALA: ECONOMIC IMPLICATIONS FOR IRAQ’S SUSTAINABLE DEVELOPMENT (2025-2027) - Obieas, Moslim Ali; Uraiby, Ahmed Obeed; Almasoodi, Muthana Faaeq (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study examines religious tourism in Karbala, Iraq as a strategic driver of economic development, analysing its multidimensional impacts and potential for sustainable growth. The research employs a mixed-methods approach using official statistical records from the Holy Abbas Shrine and the Central Bank of Iraq, applying time-series analysis on visitor data from 2016 to 2023. Findings demonstrate remarkable growth in religious tourism, with visitor numbers increasing from 11.2 million to 22 million, representing 96% growth despite temporary COVID-related declines. Statistical modeling through curve estimation provides reliable projections for 2025-2029, indicating continued growth. Economic analysis reveals that the accommodation services of tourism revenue suggest opportunities for economic diversification. The study identifies religious tourism’s distinctive characteristics, including resilience to economic fluctuations, year-round continuity with seasonal peaks, and cross-demographic appeal. The research contributes to theoretical frameworks connecting religious tourism with sustainable development while providing practical insights for policymakers. The study concludes that maximizing economic benefits requires balanced approaches, preserving Karbala’s religious identity while enhancing infrastructure and diversifying tourism-related economic activities. This research addresses significant knowledge gaps regarding religious tourism’s role in economic development within Iraq’s unique context.